Locating the microbes along the maize root system under nitrogen limitation: a root phenotypic approach - Galindo-Castañeda, Tania; Kost, Elena; Giuliano, Elena; Conz, Rafaela Feola; Six, Johan; Hartmann, Martin (Annals of botany, 2025)
A major challenge in agriculture is the low nitrogen (LN) uptake efficiency of crops, which poses environmental and economic costs. Root adaptive architectural and anatomical phenotypes in synergy with root microbes could be a promising approach to improve plant N uptake. However, little is known about such synergies. Here, we aimed to characterize the spatial distribution of the root prokaryotes of maize (Zea mays) under LN in 30 L mesocosms, where root architecture and anatomy are freely expressed, searching for correlations between prokaryotic genus abundance and 10 phenotypes. We studied the root prokaryotic community of 4-week-old plants growing in 30 L mesocosms under LN using two sandy soil mixtures. We collected root, rhizosphere, and bulk soil samples at various locations, including depths (0-20, 20-70, 70-150 cm), root classes (lateral and axial), and root types (seminal and crown). We measured plant growth response to low N availability and performed 16S rRNA gene metabarcoding on extracted DNA. Sampling location was the third most important factor after soil mixture and compartment, explaining ∼5% of the variance in root prokaryotic diversity. Seminal roots (0-20 cm depth), shallow crown roots (0-20 cm), and deep crown roots (20-150 cm) showed well-separated root microbial communities. Lateral root branching density (LRBD) explained 10% of this variance in the rhizosphere and the root tissue. We identified prokaryotic genera specific to depth, soil-root compartment, root class, and type under LN. Moreover, architectural phenotypes LRBD and lateral root length significantly correlated with the abundance of 37 genera. We highlight the importance of sampling location and architectural traits that may be associated with the microbial cycling of soil N. The exploration of synergies between root traits and microbes that participate in the N cycle has the potential to increase sustainability in agriculture.